Perlindungan Korban Tindak Kekerasan dalam Rumah Tangga (Perspektif Viktimologi dan KUHP Baru) - Hartanto; Arvita Hastarini; Dista Amelia Sontana (Universitas Ngudi Waluyo, 2023)
Households that were initially closed to authorities seem to be open now with the entry of public authorities, it is often people's awareness that even within the family there are many unsolved legal cases. Often witness and victim protection institutions that only protect criminal cases that have gone